Congregating as a social phenomenon; the social glue that binds. Issue 2 (15th February 2022) - MacCarthy, Martin; Morgan, Ashlee; Lambert, Claire
Abstract : Purpose: This study aims to consolidate and hone existing spectating and crowd theory. This is achieved by marrying socio-cultural ideas and concepts from related disciplines. Design/methodology/approach: This conceptual review examines what people do when they congregate at an event, and in doing so, answers the question of what they forgo when denied a crowd. Concepts are teased from the literature as to what happens during participatory congregation (in company, in situ ), punctuated by relegation without it. Findings: Related concepts are organised into a typology. The metamodel is the essence of the paper and includes four themes: (1) identity construction, (2) interacting with others, (3) producing and co-producing the event and (4) the allure of tribalism. Research limitations/implications: The paper is conceptual and therefore a typology (not a taxonomy). This implies that while it is likely transferable, it is not generalisable. It is manual and subjective, as opposed to objective and automatic. Notwithstanding future research implications, it is intended to inform those considering running virtual events. Practical implications: Event organisers are informed as to the "what" and "why" of running community events. It encourages a more circumspect, humanistic view that events are not merely a source of revenue. Social implications: This review contributes a macro understanding of human nature, complementing a micro understanding of crowd behaviour. Originality/value: Virtual event management is a relatively new and burgeoning field. Prior to the Pandemic an event without a crowd was almost inconceivable.